Opening up dialogues and airways: using vignettes to enrich asthma understandings in sport and exercise. Issue 4 (7th August 2016) - Allen-Collinson, Jacquelyn; Owton, Helen; Crust, Lee
Abstract: This article explores the lived experience of asthma in a specific population of sport and exercise participants, drawing on an approach currently under-utilised in studies of asthma: vignettes. These were used as an elicitation technique in research with 19 frequent exercisers and sports participants with asthma, eight of whom responded to vignettes. We describe and evaluate this approach as deployed in relation to a phenomenological study of the lived experience of asthma, and consider how employing vignette-based research can encourage people with asthma to reflect critically on their experiences and ways of being-in-the-world. This was found to be a powerful way of challenging taken-for-granted assumptions, and stimulating consideration of behaviour change. The findings we report here cohere around two principal themes that emerged as salient: (1) somatic empathy; and (2) the power of sharing stories and opening up dialogues. Understanding the complexity of asthma experiences can, we argue, be of great practical value both to those with asthma and also to healthcare and exercise professionals in tailoring more effective treatments.